Global Cities of the East: a conceptual and empirical analysis of foreign studies - Ilyassova, K.M.; Bagdatova С.А. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2021)
The article is aimed at defining the findings and concepts of the researchers of the Eastern global cities and highlighting the features of "East Asian" global cities. For the most of the twentieth century, this area was one of the least urbanized areas in the world, but now cities are growing rapidly and becoming important centers in the regional and global urban hierarchy. The researchers of the Eastern countries identified 16 major megacities claiming the title of world cities, namely Tokyo, Osaka, Kobe, Beijing, Hong Kong, Shanghai, Guangzhou, Seoul, Busan, Taipei, Singapore, Bangkok, Manila, Jakarta, Kuala Lumpur, and Istanbul. Tokyo on this list, followed by Hong Kong, is included in the "Global City", while Seoul and Taipei are included in the ranking of world cities as national models of "recently industrialized countries". These and other issues related to the global cities of the East are based on research and analysis by foreign and Russian authors.